Sequence Determinants for Regulated Degradation of Yeast 3-Hydroxy-3-Methylglutaryl-CoA Reductase, an Integral Endoplasmic Reticulum Membrane Protein - Gardner, Richard (The American Society for Cell Biology, 1998)
The degradation rate of 3-hydroxy-3-methylglutaryl CoA reductase (HMG-R), a key enzyme of the mevalonate pathway, is regulated through a feedback mechanism by the mevalonate pathway. To discover the intrinsic determinants involved in the regulated degradation of the yeast HMG-R isozyme Hmg2p, we replaced small regions of the Hmg2p transmembrane domain with the corresponding regions from the other, stable yeast HMG-R isozyme Hmg1p. When the first 26 amino acids of Hmg2p were replaced with the same region from Hmg1p, Hmg2p was stabilized. The stability of this mutant was not due to mislocalization, but rather to an inability to be recognized for degradation. When amino acid residues 27–54 of Hmg2p were replaced with those from Hmg1p, the mutant was still degraded, but its degradation rate was poorly regulated. The degradation of this mutant was still dependent on the first 26 amino acid residues and on the function of the HRD genes. These mutants showed altered ubiquitination levels that were well correlated with their degradative phenotypes. Neither determinant was sufficient to impart regulated degradation to Hmg1p. These studies provide evidence that there are sequence determinants in Hmg2p necessary for degradation and optimal regulation, and that independent processes may be involved in Hmg2p degradation and its regulation.